Supplemental Oxygen Protects Heart Against Acute Myocardial Infarction - Prabhat, Anjali M.; Kuppusamy, M. Lakshmi; Naidu, Shan K.; Meduru, Sarath; Reddy, Praneeth T.; Dominic, Abishai; Khan, Mahmood; Rivera, Brian K.; Kuppusamy, Periannan (Frontiers in Cardiovascular Medicine, 2018)
Myocardial infarction (MI), which occurs often due to acute ischemia followed by reflow, is associated with irreversible loss (death) of cardiomyocytes. If left untreated, MI will lead to progressive loss of viable cardiomyocytes, deterioration of cardiac function, and congestive heart failure. While supplemental oxygen therapy has long been in practice to treat acute MI, there has not been a clear scientific basis for the observed beneficial effects. Further, there is no rationale for the amount or duration of administration of supplemental oxygenation for effective therapy. The goal of the present study was to determine an optimum oxygenation protocol that can be clinically applicable for treating acute MI. Using EPR oximetry, we studied the effect of exposure to supplemental oxygen cycling (OxCy) administered by inhalation of 21-100% oxygen for brief periods (15-90 min), daily for five days, using a rat model of acute MI. Myocardial oxygen tension (pO2), cardiac function and pro-survival/apoptotic signaling molecules were used as markers of treatment outcome. OxCy resulted in a significant reduction of infarct size and improvement of cardiac function. An optimal condition of 30-min OxCy with 95% oxygen + 5% CO2 under normobaric conditions was found to be optimal for cardioprotection.